USE OF INTELLIGENT CONTROL SYSTEM IN LIGHTING OF PEDESTRIAN CROSSINGS TO INCREASE ENERGY EFFICIENCY - IVANOVA, MARHARYTA; OLEINIKOVA, IRYNA (Technologies and Engineering, 2022)
Purpose. Development of the concept of an intelligent control system for implementation in the scheme of pedestrian crossing lighting and design of a street lamp to reduces electricity costs and increases the service life of street lights, using technical devices such as dimmers and special motion sensors. Method. The research methods of theoretical analysis, modeling of appearance and creation of the scheme of intellectual control complex, basic provisions on lighting of pedestrian crossings and design of street lighting, analysis of possibilities of motion sensors and dimming at use in lighting are used. Results. Technologies of application of dimers and various motion sensors in lighting are analyzed and modern technological advantages of their use are allocated. Having identified a problem in the payment for electricity for street lighting for many local budgets, an intelligent control system for pedestrian crossing lighting was developed. The system allows obtaining of significant economic effect, reducing electricity consumption by a maximum of 70%. This saving is achieved by using dimming lamps and special narrow motion sensors, which have a viewing angle of 6 ° horizontally. At rest, the system keeps the lamp power at 50% until the person falls within the range of the sensor and the illumination rises to 100% for the set time. Specially selected sensors and their correct placement allow the system to work only when a person approaches a pedestrian crossing, and to remove accidental unpredictable inclusions. After analyzing the modern street lighting market, the design of a street lamp was created and proposed. Scientific novelty. It is proposed to use an intelligent control system in the lighting of pedestrian crossings, because now it is widely used only as part of the complex "smart home". Application in the scheme of lighting of pedestrian crossings of dimming and special narrowly directed motion sensors with a viewing angle of 6° horizontally that will allow to exclude accidental operation, both from people and cars, and from dogs and cats. A new design of the road lamp has been developed, based on the analyzed provisions on the correct lighting of pedestrian crossings. Practical significance. Lighting of pedestrian crossings is currently a problem in our country, because there are many accidents, and for good lighting you need to spend a lot of money on electricity from local budgets. This intelligent pedestrian crossing lighting control system is specially designed so that the use of electricity can be reduced by 70% and the service life of lamps can be significantly increased, for example by 1.5 times, but a more accurate value can be obtained only after the introduction of the first experimental sample. The use of such a system is possible throughout Ukraine at each crossing, unlike many other projects for lighting road crossings.